(untitled) (Al-Academy, 2024)
This study examines how design variables contribute to the unique identity of industrial products, focusing on how these elements interact to create a distinct product personality. It also investigates the relationship between product and user personalities, defining the former as the inherent characteristics and features of industrial products that reflect expressive traits of the user. The research identifies key factors shaping product personality, including aesthetics, form, semiotics, and technological aspects. A questionnaire distributed among design students at the College of Fine Arts, University of Baghdad, highlights the significant role of aesthetic design and brand identity in aligning products with the user’s personal taste and preferences. The findings suggest that brand, particularly in the context of mobile phones, is a crucial determinant in user selection, indicating its importance in adding value to the product and influencing consumer choice.